Analysis of pancasila teachers' teaching styles in the implementation of the independent curriculum at state junior high school 3 Karangdowo - Ayuningtyas, Dewi; Patmisari, Patmisari (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study aims to analyze the teaching style of a Pancasila Education teacher in implementing the Merdeka Curriculum at SMP Negeri 3 Karangdowo, Klaten. The research adopts a descriptive qualitative approach with an exploratory focus. Data were collected through non-participant classroom observation, structured interviews with one experienced teacher and 3 eighth-grade students, and documentation analysis including lesson plans, teaching materials, and learning outcomes. The data collection spanned six months to ensure in-depth and contextual understanding. Data validity was ensured using source, method, and time triangulation. The data analysis followed the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing with verification. The findings indicate that the teacher's instructional style under the Merdeka Curriculum is more student-centered, contextual, and engaging. However, several challenges were identified, including resistance to change, limited resources, low student motivation, and restricted instructional time. The teacher employed strategies such as differentiated instruction, character development, and the use of contextual learning with formative assessment. These findings offer theoretical contributions to Pancasila instructional strategies and practical implications for curriculum developers and educators.